Pengaruh Brand Image Terhadap Keputusan Pembelian Buah Pisang Merek Sunpride Di Toko Buah Kecamatan Ciputat Timur - Rahmalia Zachra; Dessy Iriani Putri (Jurnal Agrisep, 2026)
This study aims to analyze the effect of brand image, which consists of attribute image, benefit image, and attitude image, on purchasing decisions of Sunpride brand bananas at fruit shops in Ciputat Timur District. The research employs a quantitative method with a causal approach. Data were collected through a structured questionnaire distributed to 42 respondents who had previously purchased Sunpride bananas. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results indicate that benefit image and attitude image have a positive and significant effect on purchasing decisions, while attribute image does not have a significant effect. These findings suggest that consumers tend to place greater emphasis on perceived benefits as well as emotional attitudes and evaluations toward the brand rather than solely on the physical characteristics of the product. This study provides practical implications for fruit business practitioners and marketers, particularly Sunpride, to focus more on marketing strategies that strengthen product benefits and foster positive consumer attitudes in order to enhance purchasing decisions